OPTIMALISASI PERAN MAHASISWA DALAM MENINGKATKAN AKUNTABILITAS LAPORAN KEUANGAN BUMDES DAN UMKM - Jamingatun Hasanah; Dadang Karya Bakti; Diang Adistya; Yosby Dwi Armanza; Lisa Kurniati; Matasya Adelia Fatarani Karim; Muhammad Tauriq Shidqi Pratama; Napsiah; Sayidatina Sarah (Jurnal Mitrawarga, 2026)
The Business Administration Student Association of Lampung University conducted a community service activity in Sinar Rejeki Village, Jati Agung District, South Lampung Regency, with the aim of improving the capacity of Village-Owned Enterprises (BUMDes) and Micro, Small, and Medium Enterprises (MSMEs) in preparing transparent and accountable financial reports. The main problems encountered were low financial literacy among the community and BUMDes management that was mostly done manually and did not comply with accounting principles. The implementation method was carried out through a field study approach, literature study, Participatory Action Research (PAR), interactive discussions, and evaluation with pre-tests and post-tests. The results of the activity showed a significant increase in participants' understanding, especially regarding the importance of accountability, the preparation of simple financial reports, and the use of financial reports as a basis for business decision-making. The average increase exceeded 50% on all indicators measured. Thus, this activity succeeded in having a positive impact on the community's financial literacy and encouraged the establishment of better village financial management.